Social, lifestyle, and health status characteristics as a proxy for occupational burnout identification: A network approach analysis - Jing, Fengshi; Cheng, Mengyuan; Li, Jing; He, Chaocheng; Ren, Hao; Zhou, Jiandong; Zhou, Hanchu; Xu, Zhongzhi; Chen, Weiming; Cheng, Weibin (Frontiers in Psychiatry, 2023)
Background: Occupational burnout is a type of psychological syndrome. It can lead to serious mental and physical disorders if not treated in time. However, individuals tend to conceal their genuine feelings of occupational burnout because such disclosures may elicit bias from superiors. This study aims to explore a novel method for estimating occupational burnout by elucidating its links with social, lifestyle, and health status factors. Methods: In Below. Results: For demographic variables, age (P < 0.01) and educational background (P < 0.01) were significantly associated with occupational burnout. For work-related variables, type of position (P < 0.01) was a significant factor as well. For health & chronic diseases variables, self-rated health status, hospitalization history in the last three years, arthritis, cardiovascular diseases, high blood lipid, breast diseases, and other chronic diseases were all associated with occupational burnout significantly (P < 0.01). Breakfast frequency, dairy consumption, salt-limiting tool usage, oil-limiting tool usage, vegetable consumption, pedometer (step counter) usage, consuming various types of food (in the previous year), fresh fruit & vegetable consumption (in the previous year), physical exercise participation (in the previous year), limit salt consumption, limit oil consumption, and maintain weight were also significant factors (P < 0.01). Based on the inferred social network among all airport workers, ERGM showed that if two employees were both in the same occupational burnout status, they were more likely to share an edge (P < 0.0001). Limitation: The major limitation of this work is that the social network for occupational burnout ERGM analysis was inferred based on associated factors, such as demographics, work-related conditions, health and chronic diseases, and behaviors. Though these factors have been proven to be associated with occupational burnout, the results inferred by this social network cannot be warranted for accuracy. Conclusion: This work demonstrated the feasibility of identifying people at risk of occupational burnout through an inferred colleague’s social network. Encouraging staff with lower occupational burnout status to communicate with others may reduce the risk of burnout for other staff in the network.